2021
DOI: 10.1002/9781119507444.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Constraints on the Timing, Tempo, and Effects of Large Igneous Province Emplacement

Abstract: There is an apparent temporal correlation between large igneous province (LIP) emplacement and global environmental crises, including mass extinctions. Advances in the precision and accuracy of geochronology in the past decade have significantly improved estimates of the timing and duration of LIP emplacement, mass extinction events, and global climate perturbations, and in general have supported a temporal link between them. In this chapter, we review available geochronology of LIPs and of global extinction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 343 publications
(739 reference statements)
2
16
0
Order By: Relevance
“…To better compare the eruption rates from the two datasets, we have applied the same plotting strategy from Schoene et al (2019) to both the U−Pb and 40 Ar/ 39 Ar datasets. This approach assigns each sample to a position within a composite stratigraphic section plotted as cumulative volume and uses a Bayesian Markov Chain Monte Carlo (MCMC) algorithm to build an age model (Keller, 2018). Here, we use the assigned stratigraphic positions of the basalt samples from Fig.…”
Section: Correctly Plotting Volcanic Eruption Ratesmentioning
confidence: 99%
“…To better compare the eruption rates from the two datasets, we have applied the same plotting strategy from Schoene et al (2019) to both the U−Pb and 40 Ar/ 39 Ar datasets. This approach assigns each sample to a position within a composite stratigraphic section plotted as cumulative volume and uses a Bayesian Markov Chain Monte Carlo (MCMC) algorithm to build an age model (Keller, 2018). Here, we use the assigned stratigraphic positions of the basalt samples from Fig.…”
Section: Correctly Plotting Volcanic Eruption Ratesmentioning
confidence: 99%
“…The Snowball Earth episodes are the most extreme climate changes in Earth's history, and, yet, the triggers for their initiation remain unclear and debated. Studies of the emplacement of large igneous provinces (LIPs) have demonstrated correlations with environmental perturbations (2,3), and geochronological constraints on the older of the two episodes, the Sturtian Snowball Earth, have highlighted a possible correlation in timing of onset with the emplacement of the Franklin LIP [e.g., (4,5)].…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, geochronology studies have constrained the duration and tempo of LIP emplacement, showing that >75% of total volume is emplaced in pulses of <5 Ma, with almost all highprecision studies showing emplacement in <1 Ma (3,15). On the basis of the established rates for LIP emplacement, the actual duration of emplacement for the Franklin LIP could be only a small portion of the current range in dates, highlighting the need for higher precision and accuracy in dating.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the potential for silicic magmas to play an outsized role in driving environmental degradation during LIP emplacement is underappreciated. Because these magmas can release volatiles that reach the upper atmosphere during explosive eruptions (Robock, 2000), knowledge of the frequency and volumes of silicic volcanism is needed for a complete understanding of the relationship between LIP emplacement and mass extinctions (Courtillot and Renne, 2003;Kasbohm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%